Claiming her dignity: female resistance in the Old Testament - Claassens, L. Juliana M. (A Michael Glazier book, 2016)
Resisting the violence of war -- Resisting the violence of rape -- Resisting the violence of patriarchy heterarchy -- Resisting the violence of precarity